A DESCRIPTIVE STUDY ON THE INTEGRATION OF TECHNOLOGY AND CONTEXTUAL LEARNING IN SUPPORTING STUDENTS’ WRITING SKILLS - Mahendra, Josua; Dian Shinta Sari; Desi Sri Astuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe the integration oftechnology within the Contextual Teaching andLearning (CTL) approach in teaching descriptivewriting and its contribution to students’ writing skills ata senior high school in Sintang Regency, WestKalimantan. Despite the growing use of technology inEFL classrooms, limited studies have explored itsintegration within CTL-based writing instruction inIndonesian secondary schools. This study employed aqualitative descriptive design involving one Englishteacher and five eleventh-grade students selectedthrough purposive sampling. Data were collectedthrough classroom observation and document analysisand analyzed using thematic analysis. The findingsrevealed that technology was integrated via ChatGPT, Padlet, and Google Docs to support brainstorming, collaboration, drafting, revision, and feedback. Theintegration promoted CTL implementation andcontributed to improvements in students’ content,organization, grammar, vocabulary, and mechanics.The study concludes that purposeful technologyintegration within a CTL framework creates a moreinteractive and meaningful learning environment thatsupports students’ writing development.